Epidural Anesthesia and Staged Inodilator–Vasopressor Support for Emergency Cesarean Section in a Parturient with Severe Tricuspid Regurgitation, Pulmonary Hypertension, and Systemic Lupus Erythematosus: A Case Report - Fitri Hapsari Dewi; Propan Hanggada Satyamakti Mubarak; Aditya Baskoro (HM Publisher, 2026)
Introduction: Pregnancy imposes a progressive haemodynamic burden that can be lethal in women with fixed cardiac output states. The coexistence of severe tricuspid regurgitation, pulmonary hypertension and systemic lupus erythematosus (SLE) in a parturient is rare and carries a high risk of right ventricular decompensation, especially when an intracardiac right-to-left shunt is present. Case Presentation: We describe a 30-year-old gravida 3 para 2 woman at 37+1 weeks of gestation who presented with antepartum vaginal bleeding and known SLE, severe tricuspid regurgitation (effective regurgitant orifice area 0.4 cm², vena contracta 0.7 cm), high-probability pulmonary hypertension (estimated systolic pulmonary artery pressure 74.7 mmHg) and a patent foramen ovale with right-to-left shunt. Emergency caesarean section was performed under graded epidural anaesthesia with 0.5% levobupivacaine. Intraoperative haemodynamics were supported with titrated infusions of norepinephrine, milrinone, dobutamine and furosemide under deliberate fluid restriction. A 2.56 kg male neonate was delivered with Apgar scores of 7, 8 and 9. Transient maternal hypotension and tachycardia responded to vasoactive titration; pharmacological support was staged down and discontinued by postoperative day 2, and the patient was transferred to the ward on day 3 with an improved tricuspid regurgitant velocity. Conclusion: Graded epidural anaesthesia combined with a pathophysiology-driven, staged inodilator–vasopressor strategy and deliberate fluid restriction enabled a favourable maternal and neonatal outcome in a parturient with the tricuspid–pulmonary hypertension–lupus triad. Multidisciplinary planning and meticulous, lesion-specific haemodynamic monitoring were decisive.